1999
DOI: 10.1016/s0035-9203(99)90374-7
|View full text |Cite
|
Sign up to set email alerts
|

Histoplasmosis in eastern India: the tip of the iceberg?

Abstract: Systemic histoplasmosis has various clinical presentations and is of especially concern in immunocompromised patients. A high index of suspicion is required for its diagnosis. A total of 38 cases had been reported from India up to 1996. The most frequent occurrence of cases was around Calcutta in eastern India where the previous case was detected 20 years earlier. However, we have diagnosed 5 cases in the past 2 years from eastern India which are reported here. These cases may indicate under-diagnosis and unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 1 publication
3
43
0
Order By: Relevance
“…Several studies have shown the occurrence of hepatomegaly and/or high levels of AST and alanine aminotransferase in patients with histoplasmosis. 12,[14][15][16][17] Respiratory insufficiency is known to be a classic risk factor for death in patients with disseminated histoplasmosis, and this was confirmed in our study. Univariate analysis showed that serum creatinine levels > 1.5 mg/dL on hospital admission were associated with death.…”
supporting
confidence: 80%
“…Several studies have shown the occurrence of hepatomegaly and/or high levels of AST and alanine aminotransferase in patients with histoplasmosis. 12,[14][15][16][17] Respiratory insufficiency is known to be a classic risk factor for death in patients with disseminated histoplasmosis, and this was confirmed in our study. Univariate analysis showed that serum creatinine levels > 1.5 mg/dL on hospital admission were associated with death.…”
supporting
confidence: 80%
“…Although India being a nonendemic area for histoplasmosis, there have been few reports in the recent past, mainly from the eastern parts of the country. 12 The spores of H. capsulatum is commonly found in soils contaminated with bird droppings. The fungal spores were isolated from Gangetic delta soil.…”
Section: Discussionmentioning
confidence: 99%
“…The persistence of these organisms is dependent on the iron and calcium concentration in the phagosomes. 1 From the alveoli, the yeasts are transported by the phagosomes to the local draining lymph nodes...and from there hematogenous spread of these yeast infected phagosomes distribute them to the various organs of the body...resulting in disseminated histoplasmosis. Progressive disseminated histoplasmosis (PDH) can involve multiple organs, most commonly the bone marrow, spleen, liver, adrenal glands, and mucocutaneous membranes.…”
Section: Discussionmentioning
confidence: 99%